"Ain't I a Woman?": Perceived Gendered Racial Microaggressions Experienced by Black Women. (July 2016) - Lewis, Jioni A.; Mendenhall, Ruby; Harwood, Stacy A.; Browne Huntt, Margaret
This study explored the experience of gendered racial microaggressions (i.e., subtle and everyday verbal, behavioral, and environmental expressions of oppression based on the intersection of one's race and gender) among Black women at a predominantly White university. A total of 17 undergraduate, graduate, and professional students participated in one of two semistructured focus group discussions. Using dimensional analysis, three core gendered racial microaggression themes were uncovered, each with two subthemes: Projected Stereotypes (expectation of the Jezebel, expectation of the Angry Black Woman), Silenced and Marginalized (struggle for respect, invisibility), and Assumptions About Style and Beauty (assumptions about communication styles, assumptions about aesthetics). Results indicated that Black women experience microaggressions based on the stereotypes that exist about their gendered racial group. Findings support and extend the literature by developing a taxonomy of gendered racial microaggressions, which highlights intersecting forms of subtle oppression. Implications for research and practice in counseling psychology are discussed.